The Influence of Organizational Culture and Work Environment on Employee Performance with Job Satisfaction Mediation: A Systematic Review of the Literature - Karina Kemala Sari; Budi Eko Soetjipto; Madziatul Churiyah (PT. Maju Malaqbi Makkarana, 2026)
This study aims to identify, evaluate, and synthesize empirical evidence regarding the influence of Organizational Culture (OC) and Work Environment (WE) on Employee Performance (EP), as well as the mediating role of Job Satisfaction (JS). The method used is Systematic Literature Review (SLR) with the PRISMA 2020 protocol. Searches were conducted on the Scopus, Web of Science, and SINTA databases for publications in 2020–2026. Of the 350 articles identified, 36 articles met the inclusion criteria and were analyzed in depth. The results of the review found that: (1) organizational culture has a positive and significant effect on employee performance; (2) the work environment has a positive and significant effect on employee performance; (3) organizational culture has a positive and significant effect on job satisfaction; (4) the work environment has a positive and significant effect on job satisfaction; (5) job satisfaction has a positive and significant effect on employee performance; (6) job satisfaction partially mediates the influence of organizational culture on employee performance; and (7) job satisfaction mediates the influence of the work environment on employee performance. These findings make a theoretical contribution to the development of the human resource management literature and practical implications for organizations in designing employee performance improvement strategies.